1985
DOI: 10.1007/bf00547057
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lipid composition and drug metabolizing capacity of human liver

Abstract: The relationship between hepatic glycerolipids and microsomal drug-metabolizing enzymes was studied in liver biopsies from 41 subjects. The series included obese, diabetic, epileptic and chronic alcoholic patients, all of whom were hospitalized for suspected hepatic ailments (fatty liver, hepatitis or cirrhosis). Therapy with enzyme-inducing anticonvulsants was associated with high phospholipid and cytochrome P-450 and low triacylglycerol concentration in the liver. In patients with fatty liver or cirrhosis lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…When considering the structural changes of the microsomal membranal environment, one must recognize that the activities of other important enzymes are also likely to be altered. Changes in the Chol and phospholipid membrane constituents have been shown to alter the activities of drug-metabolizing enzymes, such as cytochrome P450 (33)(34)(35)(36)(37). In this regard, recent studies indicated that the activity of certain isozymes of the hepatic P450 enzyme system are selectively inhibited and/or stimulated by FB 1 (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…When considering the structural changes of the microsomal membranal environment, one must recognize that the activities of other important enzymes are also likely to be altered. Changes in the Chol and phospholipid membrane constituents have been shown to alter the activities of drug-metabolizing enzymes, such as cytochrome P450 (33)(34)(35)(36)(37). In this regard, recent studies indicated that the activity of certain isozymes of the hepatic P450 enzyme system are selectively inhibited and/or stimulated by FB 1 (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In alcoholic patients, anti-CYP2E1 and anti-CYP3A4 IgG antibodies have been detected [Lytton et al , 1999]. In addition, alterations in the lipid composition of hepatic glycerolipids have been correlated to decline in CYP450 concentrations [Savolainen et al , 1985]. In reality, a combination of several mechanisms are likely involved in the decreased metabolic ability of the liver during cirrhosis [Elbekai et al , 2004].…”
Section: Impact On Pharmacokinetic Processesmentioning
confidence: 99%
“…Estabrook & Lindenlaub 1979;Sotaniemi & Pelkonen 1987). The increase in liver protein and phospholipid concentrations in subjects treated with inducing drugs parallels the enhancement of microsomal enzyme activity as assessed by hepatic cytochrome P-450 or antipyrine kinetics (Luoma et al 1982b;Savolainen et al 1985). Microsomal inducers also influence triglyceride metabolism.…”
Section: The Effect Of Inducers On the Liver Endoplasmic Reticulummentioning
confidence: 95%
“…Microsomal inducers also influence triglyceride metabolism. They seem to promote triglyceride elimination and reduce triglyceride concentrations in human liver (Luoma et al 1983a;Savolainen et al 1985). Microsoma1 inducers also stimulate the rate-limiting enzyme of cholesterol synthesis, HMGCoA reductase, and 7a-hydroxylase, which is the rate-limiting, cytochrome P-450-linked enzyme in the synthesis of bile acids (Coyne et al 1976).…”
Section: The Effect Of Inducers On the Liver Endoplasmic Reticulummentioning
confidence: 99%
See 1 more Smart Citation